2009
DOI: 10.3748/wjg.15.1929
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of serum paraoxonase-1 activity in the evaluation of liver function

Abstract: Paraoxonase-1 (PON1) is an esterase and lactonase synthesized by the liver and found in the circulation associated with high-density lipoproteins. The physiological function of PON1 seems to be to degrade specific oxidized cholesteryl esters and oxidized phospholipids in lipoproteins and cell membranes. PON1 is, therefore, an antioxidant enzyme. Alterations in circulating PON1 levels have been reported in a variety of diseases involving oxidative stress including chronic liver diseases. Measurement of serum PO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 48 publications
(35 reference statements)
2
26
0
Order By: Relevance
“…In chronic liver diseases, oxidative stress is one of the causes of the pathophysiological changes leading to liver cirrhosis and to hepatocellular carcinoma. Because PON 1 has a protective effect against oxidative stress, it is expected that there is a relationship between this enzyme and liver injury . In all the ethanol consumption groups of our study, paraoxonase levels were significantly decreased as compared with control group.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In chronic liver diseases, oxidative stress is one of the causes of the pathophysiological changes leading to liver cirrhosis and to hepatocellular carcinoma. Because PON 1 has a protective effect against oxidative stress, it is expected that there is a relationship between this enzyme and liver injury . In all the ethanol consumption groups of our study, paraoxonase levels were significantly decreased as compared with control group.…”
Section: Discussionsupporting
confidence: 68%
“…Because PON 1 has a protective effect against oxidative stress, it is expected that there is a relationship between this enzyme and liver injury. 16 In all the ethanol consumption groups of our study, paraoxonase levels were significantly decreased as compared with control group. Previous studies showed that heavy alcohol feeding in rats significantly reduces both serum and liver paraoxonase activities with a corresponding down-regulation of paraoxonase mRNA in the liver.…”
Section: Discussionmentioning
confidence: 48%
“…Secondly, the interpretation of the physiological significance of a measurement conducted with such an unnatural substrates is questionable. In addition, the enzyme’s activity on paraoxon is strongly influenced by the PON1 192 genetic polymorphism (which is not well studied in bovine) [24]. Recent significant advances in the search for reliable PON1 lactonase activity assays may facilitate the measurement in a routine clinical chemistry laboratory setting [25].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, inhibition of liver PON-1 activity is an early biochemical change linked to increased lipid peroxidation and liver damage [34]. Notably, oxysterols increase total liver peroxides, IL-8 and CC-chemokine ligand-2 (CCL2) [35].…”
Section: Discussionmentioning
confidence: 99%